The mismatch between the health research and development (R&D) that is needed and the R&D that is undertaken: an overview of the problem, the causes, and solutions - Roderik F. Viergever (Taylor & Francis Group, 2013)
One of the most pressing global health problems is that there is a mismatch between the health research and development (R&D) that is needed and that which is undertaken. The dependence of health R&D on market incentives in the for-profit private sector and the lack of coordination by public and philanthropic funders on global R&D priorities have resulted in a global health R&D landscape that neglects certain products and populations and is characterised, more generally, by a distribution that is not ‘needs-driven’. This article provides an overview of the mismatch, its causes, and solutions.